2019
DOI: 10.1111/jgs.16085
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Caregiver Benefit From a Comprehensive Dementia Care Program: 1‐Year Results From the UCLA Alzheimer's and Dementia Care Program

Abstract: BACKGROUND/OBJECTIVES Persons with Alzheimer disease and related dementias (ADRDs) require comprehensive care that spans health systems and community‐based organizations. This study examined the clinical outcomes of a comprehensive dementia care program and identified subgroups who were more likely to benefit. DESIGN Observational, baseline and 1 year after intervention. SETTING Urban, academic medical center. PARTICIPANTS A total of 554 persons with dementia and their caregivers who had 1‐year follow‐up evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 32 publications
(49 reference statements)
1
51
0
Order By: Relevance
“…Other models include addressing the needs of family caregivers simultaneously with comprehensive disease management of people living with dementia to improve the quality of life of both 498 . Several evaluations have suggested that such approaches have considerable potential for improving outcomes for people with dementia and their family caregivers (for example, delayed nursing home admission and reduction in caregiver distress) 499‐508 . Current research is attempting to determine the feasibility of these models beyond the specialty settings in which they currently operate 509‐512 …”
Section: Caregivingmentioning
confidence: 99%
See 2 more Smart Citations
“…Other models include addressing the needs of family caregivers simultaneously with comprehensive disease management of people living with dementia to improve the quality of life of both 498 . Several evaluations have suggested that such approaches have considerable potential for improving outcomes for people with dementia and their family caregivers (for example, delayed nursing home admission and reduction in caregiver distress) 499‐508 . Current research is attempting to determine the feasibility of these models beyond the specialty settings in which they currently operate 509‐512 …”
Section: Caregivingmentioning
confidence: 99%
“…In the UCLA Alzheimer's and Dementia Care Program, dementia care management is provided by a nurse practitioner supervised by a primary care physician. After one year in the program, 58% of people living with dementia and 63% of their caregivers showed clinical benefit on validated instruments, 508 and the gross savings to Medicare on an annual basis totaled $2,404 per patient per year 585 . A similar collaborative care model in Indiana, the Healthy Aging Brain Center (HABC), resulted in gross savings of $3,474 per patient per year 502 .…”
Section: Special Report: On the Front Lines: Primary Care Physicians mentioning
confidence: 99%
See 1 more Smart Citation
“…107 A comprehensive dementia care management program using nurse practitioners to administer the care was associated with improved NPI-Q scores. 108 Caregiver education programs have also been shown to result in improved patient behavior as measured by the NPI-Q. 109…”
Section: Clinical Trials Of Nonpharmacologic Interventionsmentioning
confidence: 99%
“…22 In a large case series and cost comparisons with a matched control group, the program has demonstrated high quality, 23 reduced total Medicare costs, decreased nursing home placement compared with matched patients, 9 improved end-of-life care, 24 and improved patient and caregiver outcomes. 25 • The Integrated Memory Care Clinic is an patientcentered medical home led by advance practice nurses for persons with dementia and mild cognitive impairment that provides comprehensive primary and dementia care. 26 It was shown to provide high-quality care and is associated with low ED utilization and low rates of ambulatory-sensitive hospitalizations.…”
Section: Introductionmentioning
confidence: 99%